Multidisciplinary Taiwan consensus for the use of conventional TACE in hepatocellular carcinoma treatment - Chang, Pi-Yi; Lee, Rheun-Chuan; Liang, Po-Chin; Liu, Yi-Sheng; Chuang, Vicent P.; Wu, Ding-Kwo; Cheng, Yu-Fan; Huang, Jen-I.; Tseng, Hsiuo-Shan; Hung, Chien-Fu; Wu, Reng-Hong; Chern, Ming-Chih; et al. (Frontiers in Oncology, 2023)
Developed in early 1980s, transarterial chemoembolization (TACE) with Lipiodol was adopted globally after large-scale randomized control trials and meta-analyses proving its effectiveness were completed. Also known as “conventional TACE” (cTACE), TACE is currently the first-line treatment for patients with unresectable hepatocellular carcinoma (HCC) and delivers both ischemic and cytotoxic effects to targeted tumors. Although new technology and clinical studies have contributed to a more comprehensive understanding of when and how to apply this widely-adopted therapeutic modality, some of these new findings and techniques have yet to be incorporated into a guideline appropriate for Taiwan. In addition, differences in the underlying liver pathologies and treatment practices for transcatheter embolization between Taiwan and other Asian or Western populations have not been adequately addressed, with significant variations in the cTACE protocols adopted in different parts of the world. These mainly revolve around the amount and type of chemotherapeutic agents used, the type of embolic materials, reliance on Lipiodol, and the degree of selectiveness in catheter positioning. Subsequently, interpreting and comparing results obtained from different centers in a systematic fashion remain difficult, even for experienced practitioners. To address these concerns, we convened a panel of experts specializing in different aspects of HCC treatment to devise modernized recommendations that reflect recent clinical experiences, as well as cTACE protocols which are tailored for use in Taiwan. The conclusions of this expert panel are described herein.